Effect of Storage Condition on Seed Quality of Some Dhaincha (Sesbania spp.) Accessions (The Agriculturists, 2016)
An experiment was conducted at the Seed Pathology Laboratory, Department of Plant Pathology, Bangladesh Agricultural University, Mymensingh, to understand the effect of storage conditions on seed quality of different accessions of dhaincha (Sesbania spp.). Seeds of twenty accessions were collected and stored in a refrigerator (4°C) and laboratory at normal room temperature (25-30°C). Sprouting (%), germination (%), vigour index and the incidence of seed-borne pathogens were recorded following ISTA procedures. Germination and emergence were higher when seeds were stored in the refrigerator than those in room temperature. The vigour index was also high when the seeds were stored in a refrigerator. Fungi belonging to genera Aspergillus, Fusarium, Rhizopus, and Penicillium were associated with seeds of the different accessions of dhaincha. Seed borne infection of Fusarium sp. was highest (14%) in G-13 when seeds were stored at room temperature. It was evident from the results that the quality of the seeds of dhaincha accessions was retained for a long time when they were stored at low (around 4°C) temperature.The Agriculturists 2016; 14(1) 83-91